A comparative study of the effect of recasts and prompts in synchronous computer-mediated communication (SCMC) on students’ achievement in grammar - Samani, Ebrahim; Noordin, Nooreen (IDOSI Publications, 2013)
Perceptions of corrective feedback (CF) and different forms of giving these kinds of feedback have been on constant change throughout the history of second language acquisition (SLA). According to [1], grammar instruction can be effectively materialized by giving corrective feedback on learner’s errors while performing some communicative task. The current study was a new endeavor in revisiting the question of comparative effectiveness of two kinds of corrective feedback, recasts and prompts, with targeting new grammatical forms and using the affordances of computer- mediated communication (CMC). Thirty postgraduate students from Iran studying in non- English majors at Universiti Putra Malaysia (UPM) were involved in this study. They were randomly assigned to one of two treatment conditions (corrective feedback in the form of recasts and corrective feedback in the form of prompts) and the control group. During 4 online one- hour text- based chat sessions through Yahoo messenger, participants were given corrective feedback (recasts and prompts) while control group did not receive any kind of feedback. Findings of the study indicated that using both recasts and prompts through computer - mediated communication was effective for learning grammar. Results also showed that groups receiving feedback in the form of prompts outperformed their counterparts in the recast group. Findings of the study bear implications for different lines of research and practice in ESL/ EFL.